Kondisi Biometrik Kerang Darah, Tegillarca granosa, di Pesisir Pantai Utara Kota Banda Aceh - Ilham Zulfahmi; Kamaliah Helmi; Siti Rahmah; Neri Kautsari; Siti Maulida; Firman Muhammad Nur (Jurnal Ilmu Pertanian Indonesia, 2021)
The blood clam, Tegillarca granosa (Linnaeus, 1758) is one of the economically important aquatic organisms. Therefore, information related to biometric conditions is crucial as preventive and responsive efforts to manage blood clams. This study aims to analyze the biometric condition of blood clams collected from the northern coast of Banda Aceh City. Blood-clam samples were collected from three locations, namely Alue Naga, Tibang, and Deah Raya. A total of 300 blood clams were observed. The biometric parameters included the distribution of length and weight classes, the relationship between length and weight, condition factors, ratios, and correlations between total weight, meat weight, and shell weight were measured. The results showed that the majority of blood clams found in Deah Raya were in the smaller length and weight classes (30-32 mm and 12,25-17,24 g) compared to those found in Alue Naga (33-35 mm and 17,25-22,24 g) and Tibang (42-44 mm and 22,25-27,24 g). Despite having identical growth patterns (negative allometric) and condition-factor values, the blood clams collected from Alue Naga had higher meat weight ratios than those collected from the other two locations. The correlation values between the weight of the meat and the total weight of the blood clams collected from Deah Raya tends to be lower than those of blood clams obtained from Alue Naga and Tibang, which are 0,55; 0,81; and 0,78, respectively. Keywords: biometric, environmental factor, Deah Raya